DAMPAK KHOTBAH MASA KINI BAGI PERTUMBUHAN IMAN JEMAAT DI GKI PONDOK INDAH - Terry Kadarisman (STT Bethel The Way, 2021)
This paper aims to analyze the impact of nowadays sermons on congregations’ faith growth in Gereja Kristen Indonesia (GKI) Pondok Indah. The analysis was carried out within the scope of GKI Pondok Indah as a Protestant church. This research used a qualitative approach with the content analysis method. The observation was made by watching the rebroadcast of GKI Pondok Indah Sunday Services through the youtube platform, starting from 7 March to 4 April 2021 services. The sermon delivered at GKI Pondok Indah will be linked to research studies related to preaching and their impact on faith growth based on the supporting literature. The result of this research shows that sermon can increase faith growth because the sermon is meant to be a way to reveal God’s word in the life of believers so they can acknowledge the Bible’s truth, encourage them to do the right things, encourage them to change their perspectives of life, and encourage them to change their behaviour at last. This research concluded that sermons delivered at Gereja Kristen Indonesia Pondok Indah show an impact of nowadays preaching on congregations’ faith growth because fulfilled the four indicators that the researcher found. Keywords: Sermon, Faith Growth, Congregation.